Perioperative infarction during coronary bypass surgery: an attempt to refine the diagnostic criteria using data from a retrospective case–control study - Lars Niclauss; Liam-Kani Roulet; Piergiorgio Tozzi; Filip Dulguerov; Ziyad Gunga; Anna Nowacka; Matthias Kirsch (Journal of International Medical Research)
Objective The definition of coronary artery bypass graft (CABG)-associated myocardial infarction (MI) is controversial because the postoperative increases in cardiac enzyme activities are multifactorial in origin. Methods We performed a retrospective case–control study of patients who experienced perioperative MI (cardiac enzyme release, electrocardiographic changes, dysfunction on echocardiography) and those without ischemia to identify risk factors and enzyme activity thresholds. Results The estimated incidence of CABG-associated MI was 2.8%. The risk factors were a family history of cardiovascular disease (odds ratio (OR) 2.8), tobacco abuse (OR 3.8), recent MI (OR 3.6), and triple-vessel disease (OR 2.8). The MI group showed higher mortality (OR 2.3), prolonged intubation (OR 3.1), and a prolonged stay in intensive care (OR 4.3). The type 5 MI threshold (10 times the upper limit of the reference range (URL)) was exceeded in 88.4% (troponin I) and 96% (high-sensitivity troponin T; hs-cTnT) of patients without ischemia. Conclusions The frequent exceeding of conventional MI-indicating thresholds in patients without ischemia indicates their low specificity. An enzyme activity increase alone is of limited diagnostic value for perioperative MI, which is associated with greater mortality. Finally, the use of a higher threshold for hs-cTnT (>45 × URL) may increase its specificity for graft failure.